The Female Reproductive Cycle of the Neotropical Snake Atractus pantostictus (Fernandes and Puorto, 1993) from South‐eastern Brazil. (17th July 2014) - de Resende, F. C.; Nascimento, L. B.
Summary Data on reproductive activity of fossorial species are limited because the specimens are difficult to be observed and captured. Here in, we present the reproductive cycle of female Atractus pantostictus, a fossorial neotropical species, and the sexual maturity of males and females in south‐eastern Brazil. The female reproductive cycle of A. pantostictus is seasonal, with vitellogenic follicles being found from September to April and eggs in November, February, March and April with the number varying between two and four. Spermatozoa were found in the lumen of the glandular and non‐glandular uterus in females collected during the rainy season. Sperm storage tubules were found in the posterior infundibulum of the females, where the storage of sperm occurs for a short time. The storage may occur because mating and ovulation are dissociated.